(untitled) (GEON Journal (Management, Organizations and Business), 2016)
Introduction: the study of ISA 500 and the professional profile of the auditor and the auditor, It has been divided into two main areas, one related to the procedural professional profile in the audit and other professional oriented profile, which refers to the skills they should acquire the auditor to comply with the provisions of the regulation to enter into force. Justification: the realization of this study comes with the intention of investigating to near the level of updating and training in the exercise of the profession. It has a theoretical and practical connotation. Antecedent: Latin America a higher level policy development in countries such as Mexico and Costa Rica, Colombia is denoted meanwhile, is in transition period and preparation about it. Methodology: It implements a non-experimental cross-sectional design is powerful and descriptive and correlational documentary. Results: analyzing information graphically and study correlation between variables is shown. Conclusions: the research work is credited with comprehensive, coherent and relevant as a tool in the process of training and updating of the profession.